Reviews of Science for Science Librarians: Toujours, Amur! Bush Honeysuckles: Introduced, Alien, or Invasive?. Issue 1 (2nd January 2016) - Parker-Gibson, Necia
ABSTRACT: The bush honeysuckles, including Lonicera maackii, have been promulgated as horticultural prizewinners, publicized as horticultural plunderers, and occupied every step in between. Fast-spreading, relatively agnostic in terms of growing conditions, and showy, its fixed position as a decorative plant has become the root of a larger challenge. This article is a brief look at the extensive literature surrounding this ambivalent shrub.